2009
DOI: 10.1038/ejcn.2009.103
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic and insulinaemic properties of some German honey varieties

Abstract: The glycaemic and insulinaemic response to different German honey varieties have not been studied so far. Eight German honey grades differing in their floral source and carbohydrate composition were tested. Isoglucidic test meals (25 g carbohydrate) and a 25 g glucose reference were given to 10 clinically and metabolically healthy, fasting individuals (31.5±8.1 years of age (mean ± s.d.), two women). Glycaemic and insulinaemic index were calculated by the recommended FAO/WHO measure. Five of the eight tested h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 9 publications
2
36
0
3
Order By: Relevance
“…Some of these studies investigated the acute effect of honey 82, 83, 129, 133, 135, 136, 154, 155 whereas only very few studies evaluated the effect of honey over a long duration 120. This may influence the outcome, leading to significant findings in some studies and lack of significant results in others.…”
Section: Relative Strengths and Weaknesses Of Some Of These Studiesmentioning
confidence: 99%
“…Some of these studies investigated the acute effect of honey 82, 83, 129, 133, 135, 136, 154, 155 whereas only very few studies evaluated the effect of honey over a long duration 120. This may influence the outcome, leading to significant findings in some studies and lack of significant results in others.…”
Section: Relative Strengths and Weaknesses Of Some Of These Studiesmentioning
confidence: 99%
“…There is a somewhat revival for the use of honey focusing on its health promoting benefits; it has been assumed that honey has a variety of positive nutritional and health effects if consumed at levels of 50 to 80 g per serving [19]. Even though honey is a carbohydrate-rich food, its glycemic index varies across a wide range, depending on the botanical source and its glucose: fructose ratio [28]. Additionally, honey contains various oligosaccharides [6] and small amounts of proteins, enzymes, amino acids, minerals, trace elements, vitamins, …”
Section: Bioactive Ingredients Of Syhf and Their Molecular Basis For mentioning
confidence: 99%
“…A few studies have shown that honey has a low glycaemic index (GI) and peak incremental index (PII) (Deibert et al 2010;Abdulrhman et al 2011). Both GI and PII are the measures on the effects of food on the blood glucose level.…”
Section: Role Of Honey In Diabetesmentioning
confidence: 99%
“…However, the GI and PII differ between different types of honey based on different floral sources. The higher the fructose-glucose ratio of a type of honey, the lower is its GI (Deibert et al 2010). Low GI diet can improve overall glycaemic control and also reduce postprandial hyperglycaemia (Abdulrhman et al 2011).…”
Section: Role Of Honey In Diabetesmentioning
confidence: 99%